O problemie kumulacji procesowych ról świadka i biegłego. Analiza instytucji świadka-eksperta w świetle noweli procedury cywilnej - Kluska, Paulina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
This study raises the controversial issue of cumulation of procedural roles of a witness and an expert against the background of the amendment to the Code of Civil Procedure of July 4, 2019 (Journal of Laws of 2019, item 1469). Reflections on these issues began with the presentation of the views of doctrine and case-law developed on the basis of hitherto procedural reality. Subsequently, attention was devoted to regulations concerning a witness-expert and private experts in force in the legal orders of foreign countries. In addition, a new solution was analyzed both in the light of a completely different regulation of evidence from an expert opinion in simplified proceedings, as well as general provisions regulating evidence law. The perception of real threats related to the granting of the status of expert witness to the experts selected by the party, primarily from the point of view of the guarantee of the fairness of the trial (so far also signaled in the literature on the subject) was the reason to assess the legislator’s actions and to formulate postulates de lege ferenda.
Keywords: witness; expert; witness-expert; cumulation of process roles; evidences; simplified procedure; amendment; specialist news; expert opinion; private opinion; impartiality of the court expert; guarantees of process reliability